King Arthur and His Knights - Knowles, James Sir, 1831-1908.; Rhead, Louis, 1857-1926; Malory, Thomas, Sir, 15th cent. (New York : Children's Classics, 1986)
Recounts the tales of King Arthur and his knights, from the early prophecies of Merlin and Arthur's birth to the destruction of Camelot.
Based on Malory's fifteenth century Morte d'Arthur.
Keywords: Arthur, -- King; Arthurian romances -- Adaptations; Knights and knighthood -- Folklore; Folklore -- England